Climate Change and Food Systems Research: Current Trends and Future Directions. Issue 10 (October 2016) - Nelson, Michael; Zak, Kevin; Davine, Toby; Pau, Stephanie
Abstract: Rising mean temperatures, sea‐level rise, and the increasing frequencies of extreme climate events, such as drought and heat waves, are expected to destabilize global food systems. In response to this challenge, there has been a growing body of research seeking to address climate change impacts on food systems. To evaluate the current directions of climate change and food systems research, we undertook a literature search of 196 peer‐reviewed articles on the topic of climate change and food systems. Studies varied in scope and methodology, and many were framed in the context of food security. Three recurring themes within climate change and food systems research were identified: (1) vulnerability and adaptation, (2) sustainable food systems, and/or (3) biophysical impacts on food production. Additionally, we identified research gaps and discernible directions for future research. Our synthesis suggests that much of the current climate change and food systems research neglects systems‐based perspectives to conceptualizing problems and solutions, there is little consideration of the differential impacts of biophysical drivers and associated outcomes in different regions, and finally, there is a lack of critical perspectives addressing underlying political structures that maintain current food systems. We suggest that future research bridge these gaps if we are to adequately address the inherently complex nature of food systems under a changing climate.